Attitudes and behaviors of individuals aged 90 and over towards rational use of drugs: cross-sectional research - Recep Bentli; Serdar Deniz; Neşe Karakaş (SERNEV, 2023)
Introduction: The current study was aimed to evaluate the attitudes and behaviors of individuals 90 years and older living in Malatya regarding rational drug use.Methods: This cross-sectional, descriptive study was carried out with people aged 90 and over (n=1022) living in Malatya province and its districts. Face-to-face interview method was used to collect study data. In the first part of the form used for data collection, the descriptive characteristics of the participants were questioned, and in the second part, the attitudes and behaviors towards rational drug use were examined. Rational drug use features are evaluated by World Health Organization (WHO) prescribing indicators.Results: The frequency of rational drug use was 84.1%, and the rate of over-the-counter drug use was 19.2% among individuals 90 years and older. 52.3% of the participants had over-the-counter medication at home for use, when necessary, without doctor's recommendation. The most commonly available over-the-counter group of drugs at home were painkillers.Conclusion: The frequency of rational drug use in individuals aged 90 and older has been determined higher than in the literature on individuals aged 65 and older. Education, guidance and counseling programs can be created to increase rational drug use within elderly people communities.Keywords: rational drug use; oldest-old; elderly; attitude; behavior